Beyond The Domestic Space: The Beauty Of Women In Hijab In The Commercials - Qudratullah; Abd Malik, Ikmal (Sunan Kalijaga State Islamic University & The Asia Foundation, 2024)
In advertisements, women are close to the role of models of the products offered. It is because women are considered to have many attractions. This article explores the meaning of the beauty of women wearing the hijab in the Wardah cosmetic advertisement version